Experimental investigation of scour of sand beds by submerged circular vertical turbulent jets. (1st August 2022) - Chen, Jiaqi; Zhang, Gonghe; Si, Jin-Hua; Shi, Hongbo; Wang, Xikun
Abstract: The present work investigated the development of sand bed scour by submerged circular impinging vertical turbulent jets over a wide regime of jet diameters, exit velocities and impinging distances. The scour hole profiles were recorded with the optical method in order to present dynamic scour hole characteristics and their variation with any time. The results revealed that the scour profiles in the equilibrium state are similar and the geometries of the sour hole in the jet central region are only determined primarily by jet momentum flux. A semi-empirical equation has been developed for the maximum dimensionless scour depth in equilibrium state based on the obtained experimental data and theoretical analysis. The evolution of scour hole is found to be logarithmic, and three phases of temporal evolution were further distinguished. Finally, models for the prediction of variation of scour depth with time have been developed and validated, which could be used to assess the scour effects generated by impinging turbulent jets. The overall temporal evolution of the scour depth can be predicted by the erosion parameter E c and the dimensionless time to reach equilibrium τ ∞, which is superior to existing models in predicting the scouring process. Highlights: The scour hole profiles were recorded with the optical method in order to present dynamic scour hole characteristics. A semi-empirical equation has been developed for the maximum dimensionless scour depth in equilibrium state. Models for the prediction of variation of scour depth with time have been developed and validated.